High thermal conductive gasket for double-sided heat dissipation power module and preparation method thereof
Patent Information
- Application Number
- CN202611368328.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-16
AI Technical Summary
此类工艺虽然能够形成基本成形产品,但在材料致密性、晶体组织优化以及热导率提升方面仍存在一定局限,尤其在对热传导性能要求极高的场景中,往往难以兼顾高导热率、尺寸稳定性和后续加工适配性
[0017] The beneficial effects of this invention are that the high thermal conductivity pad and its preparation method for the double-sided heat dissipation power module adopt the upward continuous casting process in conjunction with a graphite crucible to effectively eliminate the risk of copper liquid oxidation and gas absorption, greatly reducing lattice defects. Under continuous extrusion, the cast microcrystals undergo secondary grain refinement and recrystallization under strong shear plastic deformation, forming a fine-grained structure with an average grain size of no more than 60 μm. This completely eliminates coarse columnar crystals and local stress concentration, as well as micropores and casting shrinkage cavities, significantly increasing the mean free path of electrons and heat sources. The thermal conductivity and electrical conductivity of the pad are both superior to those of traditional TU00 oxygen-free copper materials.
Smart Images

Figure CN122918367A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermal management materials technology, specifically relating to a high thermal conductivity pad for a double-sided heat dissipation power module and its preparation method. Background Technology
[0002] With the rapid development of electronic information technology, the power density of electronic devices continues to rise, and the local heat flux density can reach hundreds of watts per square centimeter. As a key material connecting the copper-clad ceramic substrate and the chip in a double-sided heat dissipation power module, the thermal conductivity of the pad directly determines the thermal stability and reliability of the system.
[0003] Copper, due to its excellent thermal conductivity, electrical conductivity, ductility, and processing properties, has long been widely used. However, the requirements for thermal conductivity, microstructure uniformity, and processing stability of traditional copper gaskets are constantly increasing. Existing copper materials used for gaskets are typically prepared using conventional casting, rolling, stamping, machining, or simple annealing processes. While these processes can create basically shaped products, they still have limitations in terms of material density, crystal structure optimization, and thermal conductivity improvement. Especially in scenarios with extremely high requirements for thermal conductivity, it is often difficult to simultaneously achieve high thermal conductivity, dimensional stability, and compatibility with subsequent processing. Some products may also have problems such as high oxygen content, residual impurities, and numerous internal defects, leading to unstable thermal conductivity and insufficient batch-to-batch consistency.
[0004] Therefore, overcoming the defect of unstable thermal conductivity of copper pads under existing processes is a technical problem that urgently needs to be solved in this field.
[0005] It should be noted that the information disclosed in this background section is only for understanding the background technology of the present application concept, and therefore, the above description is not considered to constitute prior art information. Summary of the Invention
[0006] This disclosure provides at least one high thermal conductivity pad for a double-sided heat dissipation power module and a method for preparing the same.
[0007] In a first aspect, the present disclosure provides a method for preparing a high thermal conductivity pad for a double-sided heat dissipation power module, comprising the following steps: S1, continuous casting: using cathode electrolytic copper plate as raw material, copper liquid is obtained by melting, deoxidizing and purifying in a melting furnace with a graphite crucible, the copper liquid is cooled and solidified by upward casting through a crystallizer, and the solidified metal is pulled out by periodic pulse traction to obtain a high-purity, low-oxygen small-grain copper billet; S2, continuous extrusion: the small-grain copper billet is fed into a continuous extrusion press, and after extrusion and demolding, it is rapidly depressed. S3, drawing and cutting: the copper busbar blank is continuously drawn, and the first and second heat dissipation surfaces are finely shaped and reduced in diameter, and then cut to length to obtain a gasket blank; S4, electroplating and slitting: the gasket blank is pre-treated on the surface, and then an electroplating layer is formed on the first and second heat dissipation surfaces, and then slitting according to size to obtain a high thermal conductivity gasket for double-sided heat dissipation power modules.
[0008] In one optional embodiment, the copper mass fraction of the cathode electrolytic copper plate in S1 is not less than 99.99%, and the temperature of the copper liquid is 1140-1200°C.
[0009] In one optional embodiment, the cooling circulating water pressure of the crystallizer in S1 is controlled at 0.4–0.7 MPa, and the temperature difference between the inlet and outlet of the cooling circulating water is 7–12°C; the graphite crucible is a high-density, low-porosity graphite crucible with a density ≥1.91 g / cm³. 3 The furnace was surrounded by inert gas.
[0010] In one optional embodiment, the average grain size of the small-grained copper billet is ≤1mm, the oxygen content is <3ppm, and the copper content is ≥99.9955%.
[0011] In one optional embodiment, the extrusion speed of the continuous extruder in S2 is 4-10 r / min, the extrusion ratio is controlled at 3-12, and the extrusion gap is controlled at 0.4-0.9 mm; the cooling uses a mixed solution of anhydrous ethanol / copper-based material antioxidant and water as the cooling medium, and the anhydrous ethanol / copper-based material antioxidant accounts for 2-5% of the mass of the cooling medium.
[0012] In one optional embodiment, the average grain size of the copper busbar is ≤60μm, and the thickness difference between the edge and the center line is no more than 0.1mm.
[0013] In one optional embodiment, the drawing speed of the drawing process in S3 is 4 to 9 m / min, and the tensile elongation is 1 to 4%; the length of the gasket blank is 0.5 to 2 m, the flatness is ≤2 mm / m, and the twist is ≤0.5° / m; the surface roughness Ra of the first heat dissipation surface and the second heat dissipation surface is ≤0.4 μm.
[0014] In an optional embodiment, the pretreatment in S4 includes sequentially degreasing, washing, activation, washing, and drying the gasket blank; wherein, degreasing is performed using a sodium hydroxide solution with a mass concentration of 10-15 g / L as the degreasing solution, the treatment temperature is 45-65°C, and the treatment time is 1-5 min; activation is performed using a dilute sulfuric acid solution with a volume fraction of 3-8% for acid washing activation, and etching is performed at room temperature for 15-80 s.
[0015] In one optional embodiment, the electroplated layer in S4 includes at least one of a nickel plating layer, a tin plating layer, a silver plating layer, a gold plating layer, and a nickel-phosphorus alloy plating layer, wherein the thickness of the electroplated layer is 3–30 μm; and the cathode current density of the electroplating process is 0.5–4.0 A / dm². 2 The electroplating temperature is 20–70℃, and the electroplating time is 5–35 min.
[0016] Secondly, embodiments of this disclosure also provide a high thermal conductivity pad for a double-sided heat dissipation power module, which is prepared by the method described above. The high thermal conductivity pad for the double-sided heat dissipation power module has a thermal conductivity ≥405W / m·K and an electrical conductivity ≥101.5%IACS.
[0017] The beneficial effects of this invention are that the high thermal conductivity pad and its preparation method for the double-sided heat dissipation power module adopt the upward continuous casting process in conjunction with a graphite crucible to effectively eliminate the risk of copper liquid oxidation and gas absorption, greatly reducing lattice defects. Under continuous extrusion, the cast microcrystals undergo secondary grain refinement and recrystallization under strong shear plastic deformation, forming a fine-grained structure with an average grain size of no more than 60 μm. This completely eliminates coarse columnar crystals and local stress concentration, as well as micropores and casting shrinkage cavities, significantly increasing the mean free path of electrons and heat sources. The thermal conductivity and electrical conductivity of the pad are both superior to those of traditional TU00 oxygen-free copper materials.
[0018] Other features and advantages of the invention will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other advantages of the invention are realized and obtained through the structures particularly pointed out in the description and the drawings.
[0019] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, preferred embodiments are described below in detail with reference to the accompanying drawings. Attached Figure Description
[0020] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0021] Figure 1 A crystal phase diagram of a small-grained copper billet after upward continuous casting is provided in an embodiment of this disclosure; Figure 2 A photograph of a continuously extruded copper busbar provided in an embodiment of this disclosure; Figure 3 A crystal phase diagram of a continuously extruded copper busbar provided in an embodiment of this disclosure; Figure 4 A photograph of a drawn copper busbar billet provided in an embodiment of this disclosure; Figure 5 This report presents a test result of the thermal conductivity of a high thermal conductivity pad for a double-sided heat dissipation power module at room temperature, provided as an embodiment of this disclosure. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] Generally speaking, the thermal conductivity of copper materials is not only related to their purity, but also closely related to their internal grain size, crystal orientation distribution, impurity content, porosity defects, and the microstructure formed during processing. If the copper material is not properly controlled during smelting, forming, or heat treatment, problems such as uneven grain size, microstructure segregation, and large residual stress can easily occur, leading to a decrease in thermal conductivity and making it difficult to meet the requirements of high-performance heat dissipation structures.
[0024] Furthermore, copper pads are often used in conjunction with chips, alumina, sintered layers, or other structural layers in practical applications. If the thermal conductivity of the copper material itself is insufficient, or if its internal structure is not dense or uniform enough, it will increase the overall thermal resistance, weaken the heat transfer capacity of the heat dissipation path, and may cause interfacial thermal stress concentration under thermal cycling conditions, affecting the reliability of the device.
[0025] The shortcomings of the above solutions are the result of the inventor's practical experience and careful research. Therefore, the discovery process of the above problems and the solutions proposed in this disclosure below should be considered as the inventor's contribution to this disclosure.
[0026] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
[0027] The following detailed description of some embodiments of the present invention is provided in conjunction with the accompanying drawings. Unless otherwise specified, the following embodiments and features can be combined with each other.
[0028] This disclosure provides a method for preparing a high thermal conductivity pad for a double-sided heat dissipation power module, comprising the following steps: S1, continuous casting: using cathode electrolytic copper plate as raw material, copper liquid is obtained by melting, deoxidation and purification in a melting furnace with a graphite crucible, the copper liquid is cooled and solidified by upward drawing through a crystallizer, and the solidified metal is pulled out by periodic pulse traction to obtain a high-purity, low-oxygen small-grain copper billet; S2, continuous extrusion: the small-grain copper billet is fed into a continuous extrusion press, and after extrusion and die extrusion, it is rapidly cooled to form a copper busbar billet with finer grains; the copper busbar billet has a first heat dissipation surface and a second heat dissipation surface arranged parallel to each other; S3, drawing and cutting: the copper busbar billet is continuously drawn, and the first heat dissipation surface and the second heat dissipation surface are finely trimmed, shaped and reduced in diameter, and then cut to length to obtain a pad blank; S4, electroplating and slitting: the surface of the pad blank is pretreated, and then an electroplating layer is formed on the first heat dissipation surface and the second heat dissipation surface, and then cut to size to obtain a high thermal conductivity pad for a double-sided heat dissipation power module.
[0029] In some embodiments, specifically, the copper mass fraction of the cathode electrolytic copper plate in S1 is not less than 99.99%, and the temperature of the copper liquid is 1140-1200°C.
[0030] In some embodiments, specifically, the cooling circulating water pressure of the crystallizer in S1 is controlled at 0.4–0.7 MPa, and the temperature difference between the inlet and outlet of the cooling circulating water is 7–12°C; the graphite crucible is a high-density, low-porosity graphite crucible with a density ≥1.91 g / cm³. 3 The furnace was surrounded by inert gas.
[0031] In some embodiments, specifically, the average grain size of the small-grained copper billet is ≤1mm, the oxygen content is <3ppm, and the copper content is ≥99.9955%.
[0032] In some embodiments, specifically, the extrusion speed of the continuous extruder in S2 is 4-10 r / min, the extrusion ratio is controlled at 3-12, and the extrusion gap is controlled at 0.4-0.9 mm; the cooling uses a mixed solution of anhydrous ethanol / copper-based material antioxidant and water as the cooling medium, and the anhydrous ethanol / copper-based material antioxidant accounts for 2-5% of the mass of the cooling medium.
[0033] Specifically, the core active ingredient of the copper-based material-specific antioxidant is any one of BTA (benzotriazole), TTA (methylbenzotriazole), and MBT (sodium mercaptobenzothiazole).
[0034] In some embodiments, specifically, the average grain size of the copper busbar is ≤60μm, and the thickness difference between the edge and the center line is no more than 0.1mm.
[0035] In some embodiments, specifically, the drawing speed of the drawing process in S3 is 4 to 9 m / min, and the tensile elongation is 1 to 4%; the length of the gasket blank is 0.5 to 2 m, the flatness is ≤2 mm / m, and the twist is ≤0.5° / m; the surface roughness Ra of the first heat dissipation surface and the second heat dissipation surface is ≤0.4 μm.
[0036] In some embodiments, specifically, the pretreatment in S4 includes sequentially degreasing, washing, activation, washing, and drying the gasket blank; wherein, degreasing uses a sodium hydroxide solution with a mass concentration of 10-15 g / L as the degreasing solution, the treatment temperature is 45-65°C, and the treatment time is 1-5 min; activation uses a dilute sulfuric acid solution with a volume fraction of 3-8% for acid washing activation, and immersion treatment at room temperature for 15-80 s.
[0037] In some embodiments, specifically, the electroplated layer in S4 includes at least one of a nickel plating layer, a tin plating layer, a silver plating layer, a gold plating layer, and a nickel-phosphorus alloy plating layer, wherein the thickness of the electroplated layer is 3–30 μm; and the cathode current density of the electroplating process is 0.5–4.0 A / dm². 2 The electroplating temperature is 20–70℃, and the electroplating time is 5–35 min.
[0038] This disclosure also provides a high thermal conductivity pad for a double-sided heat dissipation power module, which is prepared by the method described above. The high thermal conductivity pad for the double-sided heat dissipation power module has a thermal conductivity ≥405W / m·K and an electrical conductivity ≥101.5%IACS.
[0039] Example 1: A method for preparing a high thermal conductivity pad for a double-sided heat dissipation power module, comprising the following steps: S1, Upward continuous casting: Using cathode electrolytic copper plates with a copper mass fraction of not less than 99.99% as raw materials, nitrogen is filled in a melting furnace with a graphite crucible as a protective atmosphere to melt, deoxidize and purify to obtain copper liquid at 1150℃. The copper liquid is cooled and solidified upward through the cooling medium in the crystallizer. The solidified metal is pulled out by periodic pulse traction to obtain a high-purity, low-oxygen small-grain copper billet. The cooling circulating water pressure of the crystallizer is controlled at 0.4 MPa, and the temperature difference between the inlet and outlet of the cooling circulating water is 8°C. Periodic pulse traction includes pulling, stopping, and pushing, with an average traction speed of 117 mm / min; Please see Figure 1 ,like Figure 1 As shown, the grain sizes of the small-grained copper billets are 807.36μm, 872.52μm, and 1088.45μm, respectively, with an average size of less than 1mm; S2, Continuous extrusion: A small-grained copper billet is fed into a continuous extrusion press, and after being extruded and demolded, it is rapidly cooled to form a copper busbar billet with finer grains; the copper busbar billet has a first heat dissipation surface and a second heat dissipation surface arranged parallel to each other; The continuous extrusion press has an extrusion speed of 4 r / min, an extrusion ratio of 4, and an extrusion gap of 0.5 mm. A mixed solution of anhydrous ethanol and water is used as the cooling medium, wherein the anhydrous ethanol accounts for 3% of the mass of the cooling medium; The maximum thickness difference between the edge and centerline of the copper busbar is 0.05 mm, and the average grain size is less than 60 μm. S3, drawing and cutting: The copper busbar blank is continuously drawn, and the first heat dissipation surface and the second heat dissipation surface are finely shaped and reduced in diameter to obtain the gasket blank. The drawing speed of the drawing process is 4m / min, and the tensile elongation is 1.5%; the length of the gasket blank is 1m, the straightness is ≤1mm / m, and the twist is ≤0.2° / m; the surface roughness Ra of the first heat dissipation surface and the second heat dissipation surface is ≤0.3μm.
[0040] S4, Electroplating and Slitting: The gasket blank undergoes surface pretreatment, then an electroplating layer is formed on the first and second heat dissipation surfaces, followed by slitting according to dimensions to obtain the following: Figure 4 The double-sided heat dissipation power module shown uses a high thermal conductivity pad; The pretreatment includes sequentially degreasing, washing, activating, washing and drying the gasket blank; wherein, degreasing is performed using a sodium hydroxide solution with a mass concentration of 10 g / L as the degreasing solution, the treatment temperature is 60℃ and the treatment time is 4 min; the activation is performed using a dilute sulfuric acid solution with a volume fraction of 4% for acid washing activation, and immersion treatment is performed at room temperature for 70 s; The electroplating layer consists of a nickel base plating layer and a silver main plating layer, with thicknesses of 2.5 μm and 6 μm, respectively; and the cathode current density for nickel electroplating is 3.0 A / dm². 2 The electroplating temperature was 55℃, and the electroplating time was 5 minutes; the cathode current density for silver electroplating was 1.0 A / dm³. 2 The electroplating temperature was 35℃ and the electroplating time was 8 minutes.
[0041] Example 2: A method for preparing a high thermal conductivity pad for a double-sided heat dissipation power module, comprising the following steps: S1, Upward continuous casting: Using cathode electrolytic copper plates with a copper mass fraction of not less than 99.99% as raw materials, nitrogen is filled in a melting furnace with a graphite crucible as a protective atmosphere to melt, deoxidize and purify to obtain copper liquid at 1170℃. The copper liquid is cooled and solidified upward through the cooling medium in the crystallizer. The solidified metal is pulled out by periodic pulse traction to obtain a high-purity, low-oxygen small-grain copper billet. The cooling circulating water pressure of the crystallizer is controlled at 0.6 MPa, and the temperature difference between the inlet and outlet of the cooling circulating water is 11°C. Periodic pulse traction includes pulling, stopping, and pushing, with an average traction speed of 140 mm / min; The average grain size of the small-grained copper billet is less than 1 mm; S2, Continuous extrusion: A small-grained copper billet is fed into a continuous extrusion press, and after being extruded and demolded, it is rapidly cooled to form a copper busbar billet with finer grains; the copper busbar billet has a first heat dissipation surface and a second heat dissipation surface arranged parallel to each other; The continuous extrusion press has an extrusion speed of 6 r / min, an extrusion ratio of 6, and an extrusion gap of 0.6 mm. A mixed solution of a copper-based material-specific antioxidant and water is used as a cooling medium. The core active ingredient of the copper-based material-specific antioxidant is BTA, and the copper-based material-specific antioxidant accounts for 5% of the mass of the cooling medium. Please see Figure 2 and Figure 3 As shown in the figure, the macroscopic surface of the copper busbar is smooth and there is no obvious oxidation discoloration. The maximum thickness difference between the edge and the center line is 0.08 mm. The two lengths marked are 49.22 μm and 66.30 μm, respectively. It can be seen that the grain size is basically within this range, that is, the average size is less than 60 μm. S3, drawing and cutting: The copper busbar blank is continuously drawn, and the first heat dissipation surface and the second heat dissipation surface are finely shaped and reduced in diameter to obtain the gasket blank. The drawing speed of the drawing process is 7m / min, and the elongation is 2.5%; the length of the gasket blank is 1m, the straightness is ≤2mm / m, and the twist is ≤0.5° / m; the surface roughness Ra of the first heat dissipation surface and the second heat dissipation surface is ≤0.4μm.
[0042] S4, Electroplating and Slitting: The gasket blank undergoes surface pretreatment, then an electroplating layer is formed on the first and second heat dissipation surfaces, followed by slitting according to dimensions to obtain the following: Figure 4 The double-sided heat dissipation power module shown uses a high thermal conductivity pad; The pretreatment includes sequentially degreasing, washing, activating, washing and drying the gasket blank; wherein, the degreasing uses a sodium hydroxide solution with a mass concentration of 12 g / L as the degreasing solution, the treatment temperature is 50℃ and the treatment time is 2 min; the activation uses a 5% volume fraction dilute sulfuric acid solution for acid washing activation, and is immersed at room temperature for 50 s. The electroplating layer consists of a nickel base plating layer and a gold main plating layer, with thicknesses of 4 μm and 0.1 μm, respectively; and the cathode current density for the nickel plating is 3.5 A / dm². 2 The electroplating temperature was 55℃, and the electroplating time was 6 minutes; the cathode current density for gold electroplating was 0.5 A / dm³. 2 The electroplating temperature was 65℃ and the electroplating time was 0.5min.
[0043] Example 3: A method for preparing a high thermal conductivity pad for a double-sided heat dissipation power module, comprising the following steps: S1, Upward continuous casting: Using cathode electrolytic copper plates with a copper mass fraction of not less than 99.99% as raw materials, nitrogen is filled in a melting furnace with a graphite crucible as a protective atmosphere to melt, deoxidize and purify to obtain copper liquid at 1180℃. The copper liquid is cooled and solidified upward through the cooling medium in the crystallizer. The solidified metal is pulled out by periodic pulse traction to obtain a high-purity, low-oxygen small-grain copper billet. The cooling circulating water pressure of the crystallizer is controlled at 0.7 MPa, and the temperature difference between the inlet and outlet of the cooling circulating water is 10°C. Periodic pulse traction includes pulling, stopping, and pushing, with an average traction speed of 124 mm / min; The average grain size of the small-grained copper billet is less than 1 mm; S2, Continuous extrusion: A small-grained copper billet is fed into a continuous extrusion press, and after being extruded and demolded, it is rapidly cooled to form a copper busbar billet with finer grains; the copper busbar billet has a first heat dissipation surface and a second heat dissipation surface arranged parallel to each other; The continuous extrusion press has an extrusion speed of 8 r / min, an extrusion ratio of 8, and an extrusion gap of 0.8 mm. A mixed solution of a copper-based material-specific antioxidant and water is used as a cooling medium. The core active ingredient of the copper-based material-specific antioxidant is TTA, and the copper-based material-specific antioxidant accounts for 5% of the mass of the cooling medium. The maximum thickness difference between the edge and centerline of the copper busbar is 0.07 mm, and the average grain size is less than 60 μm. S3, drawing and cutting: The copper busbar blank is continuously drawn, and the first heat dissipation surface and the second heat dissipation surface are finely shaped and reduced in diameter to obtain the gasket blank. The drawing speed of the drawing process is 9 m / min, and the tensile elongation is 3%; the length of the gasket blank is 1 m. Please see Figure 4 As shown in the figure, the copper busbar blank after drawing has a smooth surface with a straightness ≤1mm / m and a twist ≤0.2° / m; the surface roughness Ra of the first heat dissipation surface and the second heat dissipation surface is ≤0.3μm; S4, Electroplating and Slitting: The gasket blank undergoes surface pretreatment, then an electroplating layer is formed on the first and second heat dissipation surfaces, followed by slitting according to dimensions to obtain the following: Figure 4 The double-sided heat dissipation power module shown uses a high thermal conductivity pad; The pretreatment includes sequentially degreasing, washing, activation, washing, and drying the gasket blank; wherein, degreasing is performed using a sodium hydroxide solution with a mass concentration of 15 g / L as the degreasing solution, the treatment temperature is 45°C, and the treatment time is 2 min; activation is performed using a 6% (v / v) dilute sulfuric acid solution for acid washing and activation, and immersion treatment is performed at room temperature for 35 s; The electroplating layer consists of a nickel undercoat and a tin plating layer, with thicknesses of 3 μm and 6 μm, respectively; and the cathode current density for the nickel plating is 3.0 A / dm². 2 The electroplating temperature was 55℃, and the electroplating time was 5 minutes; the cathode current density for tin electroplating was 2.0 A / dm³. 2 The electroplating temperature is 25℃ and the electroplating time is 5 minutes.
[0044] The high thermal conductivity pads used in the double-sided heat dissipation power modules obtained in Examples 1-3 were tested for thermal conductivity according to the specifications of GB / T22588, which specifies the measurement of thermal diffusivity or thermal conductivity using the flash method. Please refer to [link to relevant documentation]. Figure 5 As shown in the figure, the thermal conductivity of Example 1 was 410.476 W / m·K. The copper content, oxygen content and electrical conductivity of Examples 1-3 were further tested according to the provisions of GB / T 5121 Chemical Analysis Methods for Copper and Copper Alloys and GB / T 32791 Eddy Current Test Method for Electrical Conductivity of Copper and Copper Alloys. The complete test results are shown in Table 1 below.
[0045]
[0046] Comparative Example 1, a method for preparing gaskets based on traditional copper materials, includes the following steps: S1, Continuous casting: Using cathode electrolytic copper plates with a copper mass fraction of not less than 99.99% as raw materials, the copper is melted and solidified in a non-sealed furnace structure to obtain a copper billet; the copper billet has a first heat dissipation surface and a second heat dissipation surface arranged parallel to each other; S2, Drawing and Cutting: The copper billet is drawn and cut to obtain the gasket blank; S3, Electroplating and Slitting: The surface of the gasket blank is pretreated, and then an electroplating layer is formed on the first heat dissipation surface and the second heat dissipation surface. Then it is slitted according to size to obtain the gasket.
[0047] Comparative Example 1 gasket performance results: copper content 99.98wt%, oxygen content >10ppm, thermal conductivity 357W / m·K, electrical conductivity 100%IACS.
[0048] Continuous casting employs a non-sealed brick furnace structure. Compared to graphite crucible systems, the bricks are more prone to reacting with the melt at high temperatures, becoming nuclei for foreign inclusions. Simultaneously, the non-sealed furnace structure exacerbates secondary oxidation of the melt, resulting in a significantly higher oxygen content compared to graphite crucible systems. By omitting the extrusion process, casting produces internal voids such as micropores and shrinkage cavities, which disrupt the material's continuous conductive pathways, reducing effective heat and electrical conductivity. Compared to fine-grained homogeneous materials, this results in lower thermal and electrical conductivity.
[0049] Comparative Example 2, a gasket preparation method based on traditional copper materials, includes the following steps: S1, Downward Semi-continuous Casting: Using cathode electrolytic copper plates with a copper mass fraction of not less than 99.99% as raw materials, copper billets are solidified by downward semi-continuous casting. S2, hot extrusion: hot extrusion of copper billet, followed by rapid cooling after extrusion through a die to obtain copper busbar blank; the copper busbar blank has a first heat dissipation surface and a second heat dissipation surface arranged parallel to each other. S3, Stamping: Stamping the copper casting billet to obtain the gasket blank; S3, Electroplating and Slitting: First, deburr the gasket blank, then perform surface pretreatment, then form an electroplating layer on the first heat dissipation surface and the second heat dissipation surface, and then slit it according to size to obtain the gasket.
[0050] Comparative Example 2 gasket performance results: copper content 99.98wt%, oxygen content >20ppm, thermal conductivity 364W / m·K, electrical conductivity 99.8%IACS.
[0051] Compared to the gaskets produced using the upward casting and continuous extrusion processes in Examples 1-3, the comparative production process lacks a sealed, oxygen-free environment, easily leading to the formation of a brittle cuprous oxide eutectic structure. This results in uneven internal grains, micro-inclusions, and micropore defects, exacerbating electron and heat conduction scattering, and causing more significant performance degradation under high-frequency and high-temperature conditions. While stamping and deburring processes can achieve large-scale production, they require upfront mold development costs, raising the entry barrier. Furthermore, due to the internal stress in the raw materials, slight warping is prone to occur after stamping, necessitating additional grinding and leveling processes, lengthening the production process and increasing processing costs.
[0052] The gaskets obtained from Comparative Examples 1-2 were tested for copper content, oxygen content, electrical conductivity, and thermal conductivity. The complete test results are shown in Table 2 below.
[0053]
[0054] In summary, the high thermal conductivity pad and its preparation method for this double-sided heat dissipation power module, using an upward continuous casting process combined with a graphite crucible, effectively eliminate the risk of copper molten metal oxidation and gas absorption, greatly reducing lattice defects. Under continuous extrusion, the cast microcrystals undergo secondary grain refinement and recrystallization under strong shear plastic deformation, forming a fine-grained structure with an average grain size of no more than 60 μm. This completely eliminates coarse columnar crystals and local stress concentration, as well as micropores and casting shrinkage cavities, significantly increasing the mean free path of electrons and heat sources. The thermal conductivity and electrical conductivity of the pad are superior to those of traditional TU00 oxygen-free copper materials.
[0055] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A method for preparing a high thermal conductivity pad for a double-sided heat dissipation power module, characterized in that, Includes the following steps: S1, Upward continuous casting: Using cathode electrolytic copper plates as raw materials, copper liquid is obtained by melting, deoxidizing and purifying in a melting furnace with a graphite crucible. The copper liquid is cooled and solidified upward through a crystallizer. The solidified metal is pulled out by periodic pulse traction to obtain a high-purity, low-oxygen small-grain copper billet. S2, Continuous extrusion: Small-grained copper billets are fed into a continuous extrusion press, and after being extruded and demolded, they are rapidly cooled to form copper busbar billets with finer grains. The copper busbar has a first heat dissipation surface and a second heat dissipation surface arranged parallel to each other. S3, drawing and cutting: The copper busbar blank is continuously drawn, and the first and second heat dissipation surfaces are finely shaped and reduced in diameter and then cut to length to obtain the gasket blank. S4, Electroplating and Slitting: The surface of the pad blank is pretreated, and then an electroplating layer is formed on the first heat dissipation surface and the second heat dissipation surface. Then it is slitted according to size to obtain a high thermal conductivity pad for double-sided heat dissipation power module.
2. The method for preparing the thermally conductive pad as described in claim 1, characterized in that, The copper mass fraction of the cathode electrolytic copper plate in S1 is not less than 99.99%, and the temperature of the copper liquid is 1140-1200℃.
3. The method for preparing the thermally conductive pad as described in claim 1, characterized in that, The cooling circulating water pressure of the crystallizer described in S1 is controlled at 0.4-0.7 MPa, and the temperature difference between the inlet and outlet of the cooling circulating water is 7-12℃. The graphite crucible is a high-density, low-porosity graphite crucible with a density ≥ 1.91 g / cm³. 3 The furnace was surrounded by inert gas.
4. The method for preparing the thermally conductive pad as described in claim 1, characterized in that, The average grain size of the small-grained copper billet is ≤1mm, the oxygen content is <3ppm, and the copper content is ≥99.9955%.
5. The method for preparing the thermally conductive pad as described in claim 1, characterized in that, The continuous extrusion press described in S2 has an extrusion speed of 4-10 r / min, an extrusion ratio of 3-12, and an extrusion gap of 0.4-0.9 mm. The cooling process uses a mixed solution of anhydrous ethanol / copper-based material antioxidant and water as the cooling medium, wherein the anhydrous ethanol / copper-based material antioxidant accounts for 2-5% of the mass of the cooling medium.
6. The method for preparing the thermally conductive pad as described in claim 1, characterized in that, The average grain size of the copper busbar is ≤60μm, and the thickness difference between the edge and the center line is no more than 0.1mm.
7. The method for preparing the thermally conductive pad as described in claim 1, characterized in that, The drawing speed for the drawing process described in S3 is 4–9 m / min, and the tensile elongation is 1–4%. The length of the gasket blank is 0.5 to 2 m, the flatness is ≤2 mm / m, and the twist is ≤0.5° / m; The surface roughness Ra of the first heat dissipation surface and the second heat dissipation surface is ≤0.4μm.
8. The method for preparing the thermally conductive pad as described in claim 1, characterized in that, The pretreatment described in S4 includes sequentially performing degreasing, water washing, activation, water washing, and drying on the gasket blank. The degreasing process uses a sodium hydroxide solution with a mass concentration of 10–15 g / L as the degreasing liquid, the treatment temperature is 45–65℃, and the treatment time is 1–5 min. Activation is achieved by acid washing with a dilute sulfuric acid solution of 3-8% by volume, followed by immersion etching at room temperature for 15-80 seconds.
9. The method for preparing the thermally conductive pad as described in claim 1, characterized in that, The electroplating layer mentioned in S4 includes at least one of nickel plating, tin plating, silver plating, gold plating, and nickel-phosphorus alloy plating, and the thickness of the electroplating layer is 3 to 30 μm; Furthermore, the cathode current density for electroplating is 0.5–4.0 A / dm². 2 The electroplating temperature is 20–70℃, and the electroplating time is 5–35 min.
10. A high thermal conductivity pad for a double-sided heat dissipation power module, manufactured using the method described in any one of claims 1-9, characterized in that, The high thermal conductivity pad used in the double-sided heat dissipation power module has a thermal conductivity ≥405W / m·K and a conductivity ≥101.5%IACS.